THE RELATIONAL EFFECT OF THE RULE OF LAW: A COMPARATIVE STUDY OF JAPANESE AND SOUTH KOREAN FOREIGN DIRECT INVESTMENT - David W. Kunsch; Karin L. Schnarr; W. Glenn Rowe (Asian Academy of Management Journal, 2014)
Building on institutional theory, this paper examines the relationship between the relative rule of law of home and host countries, the home country's institutional frame and foreign direct investment (FDI). We suggest that firms based in countries with a higher level of rule of law will invest more FDI per capita in host countries with comparable or higher levels of legal protections. Further, companies based in countries with a lower rule of law are accustomed to lower degrees of institutional safeguards. For these latter countries, the comparable levels of rule of law between home and host country will not as strongly impact FDI per capita. We test our logic through an examination of FDI from two home countries with different levels of rule of law: Japan (high) and South Korea (medium). Using FDI data from Japanese firms in 114 countries and South Korean firms in 118 countries, we find that while rule of law is a predictor of FDI per capita, the relative nature of the rule of law between home and host countries in higher rule of law home countries is also important. In addition, we discover that companies from Japan, a high rule of law country do seek out similar or higher rule of law environments for higher levels of FDI per capita investments while companies from a medium level rule of law country, South Korea, are less beholden to institutional standards. Our study contributes to the literature looking at the impact of country-level factors on foreign investment decisions, suggesting that it is the comparative rather than absolute values that are important to understand as well as the institutional environment in the home country.